HUBUNGAN MANAJEMEN DIRI DENGAN PRESTASI BELAJAR MATEMATIKA SISWA KELAS VIII SMP NEGERI 3 WATAMPONE KABUPATEN BONE - NURWIJAYA, SUGIAN (Fakultas Tarbiyah Institut Agama Islam Negeri (IAIN) Bone, 2018)
This research is an ex-post facto study that is correlational in nature to find a causal relationship between self-management and mathematics learning achievement of eighth grade students in SMP Negeri 3 Watampone, Bone Regency. The hypothesis of this study is that there is a positive relationship between self-management and mathematics learning achievement of eighth grade students of SMP Negeri 3 Watampone. The population of this study was the eighth grade students of SMP Negeri 3 Watampone Bone Regency and the sample in this study was 122 students.The data collection technique carried out in this study was derived from self-management questionnaires distributed to 122 respondents and report card grades in mathematics subjects of SMP Negeri 3 Watampone. The results of this study reveals that the average self-management score of students is 3.67 which is in the high category with an interval of 3.4 ≤X <4.2. While the average value of student learning achievement is 80 which is in the good category with an interval score of 61 - 80. From the results of hypothesis testing shows that the correlations obtained a significant value of 0,000 (0,000≤ 0,05) which means self-management is positively related to achievement study mathematics class VIII SMP Negeri 3 Watampone, Bone Regency.